2015
DOI: 10.1186/s12939-015-0266-8
|View full text |Cite
|
Sign up to set email alerts
|

Chronic diseases among the elderly in a rural Vietnam: prevalence, associated socio-demographic factors and healthcare expenditures

Abstract: BackgroundGlobally, the population of elderly persons is increasing as well as the prevalence of chronic diseases. This change is causing increased healthcare costs to health care systems threatening to push many households into poverty. Low and middle income countries are projected to experience the greatest impact from this change. This study aims to describe the prevalence of common chronic diseases (CCDs) among the elderly in Vietnam, the associated socio-demographic factors and healthcare expenditures.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
62
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(76 citation statements)
references
References 25 publications
12
62
1
1
Order By: Relevance
“…The literature suggests that socioeconomic factors are closely associated with the health status and medication use by the elderly (44,45). Our study found that educational level, social security coverage, and profession affected the number of medications taken daily, and Haider et al (43) discovered a significant correlation between the number of medications taken daily by the elderly and their educational level.…”
Section: Discussionsupporting
confidence: 52%
“…The literature suggests that socioeconomic factors are closely associated with the health status and medication use by the elderly (44,45). Our study found that educational level, social security coverage, and profession affected the number of medications taken daily, and Haider et al (43) discovered a significant correlation between the number of medications taken daily by the elderly and their educational level.…”
Section: Discussionsupporting
confidence: 52%
“…If these families lack financial protection for health risks, high medical expenditures may plunge them into poverty. 29,30 Although the NRCMS has achieved better protection in groups with one or two chronic diseases, the protection is still insufficient in the superposition of various chronic diseases.The incidence of IME in the superimposed family reached 15.08%, which was 2.73 times that of families without chronic diseases. The OOP ratio for health services for the older adults over 45 years old in China was 55%, which was higher than the residents OOP 30% in 2016, 31 and much higher than the national average of 18.6% published by WHO in 2015.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic diseases means chronic non-communicable diseases, including coronary heart disease, hypertension, diabetes, chronic respiratory diseases, malignant tumor, characterized by insidious onset, difficulty of cure, incurable and complex etiology, clinical characteristics are high incidence, high morbidity and high mortality. The characteristics of elderly patients with chronic diseases: first, the prevalence of chronic diseases in the elderly is increasing year by year [14]. Second, it is the coexistence of 1-3 kinds of chronic diseases in the elderly.…”
Section: Discussionmentioning
confidence: 99%